Test bed for contact-mode triboelectric nanogenerator - Hong, Daewoong; Choi, Young Man; Jeong, Jaehwa (Review of Scientific Instruments, 2018)
The triboelectric nanogenerator (TENG) has become one of the strongest candidates for sustainable power sources. The power of a TENG depends on factors such as contact area, contact parallelism, contact force, and contact speed. In order to evaluate the performance of the TENG precisely and quantitatively, it is necessary to apply consistent experimental conditions and measurement processes. In this paper, we propose a test bed capable of adjusting the contact area and contact parallelism and measuring the contact force, contact speed, current, and voltage in real time. The test bed consists of a 2-axis planar stage, a 2-axis tilting stage, a 1-axis vertical stage, a 3-degree-of-freedom (DOF) force/torque sensor, a capacitive displacement sensor, and a voice coil actuator. The 3-DOF force/torque sensor can provide feedback on the degree of parallelism and contact area alignment as well as contact force. With the proposed test bed, the effects of parallelism error, contact area, contact force, and contact speed on the performance of contact-mode TENGs are quantitatively analyzed. This test bed is expected to be used for the quantitative analysis of contact-mode TENGs with various new structures and for comparison among different devices.
Keywords: Capacitive displacement sensors; Contact forces; Degree of parallelism; Experimental conditions; Force/torque sensor; Measurement process; Sustainable power; Voice coil actuators